1982
DOI: 10.1128/iai.38.2.699-705.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol on chlamydial genital infection of female guinea pigs

Abstract: Female guinea pigs were treated daily with 1 mg of beta-estradiol-3-benzoate intramuscularly beginning 14 days before intravaginal inoculation with the chlamydial agent of guinea pig inclusion conjunctivitis and continuing during the course of the infection. Treatment with estradiol was found to markedly influence the course of genital infection with the chlamydial agent of guinea pig inclusion conjunctivitis, producing infections of greater intensity and longer duration than those in control animals. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Feline C psittaci infection possibly may be influenced by the host's endocrine environment, as has been shown for chlamydial infections in other host species, including sheep, 41 humans, 42 and guinea pigs. 43,44 Conjunctival shedding of FHV1 was not detected by PCR in any cat. Assuming that some or all of these cats were latently infected with FHV1, as has been shown to occur in approximately 80% of FHV1-infected cats, 45 the stress associated with chlamydial infection appears not to be sufficient to cause herpesviral reactivation.…”
Section: Discussionmentioning
confidence: 90%
“…Feline C psittaci infection possibly may be influenced by the host's endocrine environment, as has been shown for chlamydial infections in other host species, including sheep, 41 humans, 42 and guinea pigs. 43,44 Conjunctival shedding of FHV1 was not detected by PCR in any cat. Assuming that some or all of these cats were latently infected with FHV1, as has been shown to occur in approximately 80% of FHV1-infected cats, 45 the stress associated with chlamydial infection appears not to be sufficient to cause herpesviral reactivation.…”
Section: Discussionmentioning
confidence: 90%
“…Data accumulated from clinical trials suggested that detection of chlamydial infection in female patients during the oestrogen phase of the menstrual cycle was highly predictive of upper genital tract complications, such as salpingitis (Sweet et al, 1986). Elegant studies of chlamydial infection in the guinea pig model by Rank and colleagues indicated increased intensity and duration of inflammation, fibrosis and tubal dilation when chlamydiae migrated into the upper genital tract during high oestradiol levels (Rank et al, 1982;Rank and Sanders, 1992). Guseva et al reported that both luminal and glandular epithelial cells, harvested from the cervix, uterus and uterine horns of mature female swine and grown ex vivo, were significantly more susceptible to Chlamydia suis S45 in the proliferative, oestrogen-dominant phase versus the secretory, progesterone-dominant phase (Guseva et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that male rabbits are more susceptible to the lethal effects of an infection with a TSS strain than are female rabbits and that castration abolished this difference (3). Because sex steroids have been shown by others to affect a variety of infections in other experimental animals (8)(9)(10)14), the present study was undertaken to determine whether the mortality observed in rabbits infected with a TSS strain of S. aureus could be affected by sex steroid pretreatment and whether there was a relationship between observed mortality and the circulating levels of these sex steroids. The organism used was isolated from a 14-year-old female patient by J. Todd (Children's Hospital of Denver, Denver, Colo.).…”
mentioning
confidence: 99%